2017
DOI: 10.5578/tt.27626
|View full text |Cite
|
Sign up to set email alerts
|

Association between admission neutrophil to lymphocyte ratio and outcomes in patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: Association between admission neutrophil to lymphocyte ratio and outcomes in patients with acute exacerbation of chronic obstructive pulmonary disease Introduction: The prognostic significance of neutrophil-to-lymphocyte ratio (NLR), derived-neutrophil-to-lymphocyte ratio (d-NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) have been shown in many diseases. To the best of our knowledge, there is no published report evaluation of those parameters in acute exacerbation of chronic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 38 publications
3
49
0
1
Order By: Relevance
“…Of these, 206 were excluded after initial screening. After full‐text review of the remaining 21 articles, twelve studies were excluded because they did not meet the inclusion criteria . Nine studies were included in the final analysis …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 206 were excluded after initial screening. After full‐text review of the remaining 21 articles, twelve studies were excluded because they did not meet the inclusion criteria . Nine studies were included in the final analysis …”
Section: Resultsmentioning
confidence: 99%
“…In previous years, five studies reported that NLR also represents an independent predictor of mortality in COPD patients . Two observational prospective studies found that NLR is an independent predictor of COPD exacerbation during the first‐year follow‐up, although only one of them reported statistically significant differences .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed that an increase in NLR during stable phase of COPD was correlated to lower values of inferior RNFL and In previous years, five studies reported that NLR also represents an independent predictor of mortality in COPD patients. [31][32][33][34][35] Two observational prospective studies found that NLR is an independent predictor of COPD exacerbation during the first-year follow-up, although only one of them reported statistically significant differences. 36,37 Some authors also found a moderate correlation between NLR and some functional parameters like FEV 1 and mMRC of COPD cases.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet/MPV ratio was not different between the two groups. Survival negatively influenced by elevated CRP in the non-eosinophilic group RAHIMIRAD [51] dNLR, MLR, PLR dNLR higher in dead patients than in those discharged alive. MLR and PLR not significant in multivariate analysis YAO [52] CRP, PLR NLR levels correlated with serum CRP levels in AECOPD.…”
Section: Nlr and Steroid Therapy In Copdmentioning
confidence: 99%
“…RAHIMIRAD et al [51] retrospectively reviewed 315 hospital charts of COPD patients in two Iranian hospitals. NLR values were higher in patients who died in hospital than in those discharged alive.…”
Section: Nlr As a Prognostic Marker In Copdmentioning
confidence: 99%